2022
DOI: 10.3389/fcell.2022.810980
|View full text |Cite
|
Sign up to set email alerts
|

The Signature of Moderate Perinatal Hypoxia on Cortical Organization and Behavior: Altered PNN-Parvalbumin Interneuron Connectivity of the Cingulate Circuitries

Abstract: This study was designed in a rat model to determine the hallmarks of possible permanent behavioral and structural brain alterations after a single moderate hypoxic insult. Eighty-two Wistar Han (RccHan: WIST) rats were randomly subjected to hypoxia (pO2 73 mmHg/2 h) or normoxia at the first postnatal day. The substantially increased blood lactate, a significantly decreased cytochrome-C-oxygenase expression in the brain, and depleted subventricular zone suggested a high vulnerability of subset of cell populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 97 publications
(127 reference statements)
0
5
1
2
Order By: Relevance
“…Some studies demonstrated that a reduction in PV + neurons also confirmed a reduction in Wisteria floribunda agglutinin (WFA + ) perineuronal nets (PNNs) in schizophrenia ( 83 ), which are predominantly related to a certain subpopulation of PV + neurons ( 85 ). Such findings suggested that PV + neuron loss in schizophrenia could be rather selective, targeting only specific neuronal subpopulations ( 86 ).…”
Section: Cortical Interneurons In Schizophreniamentioning
confidence: 99%
“…Some studies demonstrated that a reduction in PV + neurons also confirmed a reduction in Wisteria floribunda agglutinin (WFA + ) perineuronal nets (PNNs) in schizophrenia ( 83 ), which are predominantly related to a certain subpopulation of PV + neurons ( 85 ). Such findings suggested that PV + neuron loss in schizophrenia could be rather selective, targeting only specific neuronal subpopulations ( 86 ).…”
Section: Cortical Interneurons In Schizophreniamentioning
confidence: 99%
“…Studies that examine the role of hypoxia and HIF-1 in promoting metastasis in cancer are examples of how HIF-1 activation can regulate the expression of ECM components including MMPs to alter ECM physiology [ 79 ]. Even a single hypoxic event can induce long-lasting changes in the ECM, as demonstrated in perinatal rats which exhibited altered PNN composition in the cingulate cortex that persisted into adulthood from exposure to a single hypoxic event [ 80 ]. While some studies show a neuroprotective role for HIF-1 in neurodegeneration and brain injury, others suggest that HIF-1α might contribute to pathology [ 81 ].…”
Section: Transcriptional Regulation Of Ecm: Hif-1 Ahr and A Potential...mentioning
confidence: 99%
“…В експерименті та клінічний практиці продемонстровано пряму залежність концентрації низки нейроспецифічних білків та антитіл до них, молекулярних маркерів оксидативного стресу та мітохондріальної дисфункції у крові новонароджених від тяжкості клінічного стану [3−5]. Єдиними нейромолекулами, які здатні протистояти механізмам нейродеструкції, вважають нейротрофічні фактори та білки теплового шоку, а також фактори, індуковані гіпоксією [6,7]. Дисфункція синтезу фактора росту нервів (NGF), мозкового нейротрофічного фактора (BDNF) та нейротрофіну-3 може сприяти мозковому розвитку з ослабленою нейропластичністю, що призводить до формування церебральної недостатності у дітей, які перенесли пре-та перинатальну гіпоксію [5].…”
Section: вступunclassified
“…1; 2). Отримані результати відповідають концепції пренатального пошкодження ЦНС, що відводить важливу роль оксидативному і нітрозативному стресу при пошкодженні нейронів у новонароджених, які зазнали дії внутрішньоутробної гіпоксії [5,7]. Відомо, що гіперпродукція АФК і цитотоксичних форм монооксиду азоту (NO) на тлі антиоксидантної недостатності внаслідок окиснювальної модифікації білкових структур рецепторів, іонних каналів нейрона, порушення механізмів зворотного захоплення трансмітерів призводить до стійких порушень вищих функцій ЦНС (пам'ять, увага, здатність до навчання, аналіз отриманої інформації) у дітей, які перенесли ПГ [8].…”
Section: результати та їх обговоренняunclassified